Effect of Corticosteroids upon Fibrinogen Metabolism in Rabbits - Seligsohn, Uri; Rapaport, Samuel I.; Shen, Stephen M.-C.; Kuefler, Paul R. (Thrombosis and Haemostasis, 1973)
The effect of pharmacologic doses of adrenal corticosteroids upon plasma fibrinogen level, incorporation of 75Se-Methionine (75SeM) into fibrinogen, and disappearance of plasma 125I-fibrinogen was evaluated in rabbits. Single 25 mg doses of hydrocortisone or cortisone transiently increased both 75SeM incorporation into fibrinogen and plasma fibrinogen levels, but 1 to 5 mg doses of hydrocortisone had no significant effect upon plasma fibrinogen levels. Repeated daily injections of 25 mg of hydrocortisone did not increase plasma fibrinogen levels progressively. Two doses of 25 mg of hydrocortisone, given 24 hr apart, failed to alter the rate of disappearance of plasma 125I-fibrinogen radioactivity, i.e., plasma fibrinogen catabolism. Intramuscular injection of 2.5 ml of propylene glycol solvent caused a prolonged rise in plasma fibrinogen level, whereas injection of 25 mg of corticosterone dissolved in propylene glycol resulted in an attenuated and transient rise in plasma fibrinogen level. Apparently, the presence or absence of a coexistent inflammatory stimulus determines the overall effect of large pharmacologic doses of corticosteroids upon fibrinogen metabolism in the rabbit. In the presence of inflammation, corticosteroids decrease synthesis with a resultant fall in plasma fibrinogen level; in the absence of inflammation, corticosteroids may increase synthesis transiently with a resultant slight increase in plasma fibrinogen level.